Towards service quality improvement for passenger satisfaction at intercity express bus services / Murzamir Ahmad...[et al.] - Ahmad, Murzamir; Osman, Norhasnisam; Mukhtar, Farah Wahida (2017)
This research is about the Service Quality dimensions that become important for express bus services as a form of land public transport. The ICOP SHE 2010 emphasises good and quality service to customer in which requires the service provider to offer the best service to meet the customers’ needs. The Safety Star Grading is introduced with an indicator to determine the operational safety level and service performance of bus service providers. With poor assessment rating and no award obtained, this research is to identify the possible causes in business operations and determine the service quality improvement for InterCity Express Bus. Four (4) components of key research areas consist of business tools namely SWOT Analysis, Fishbone Analysis, Benchmarking and Passenger Satisfaction Survey have been used in this study. Service quality dimensions of reliability, responsive, safety and tangible are used for this study. The outcome of this study supports the company to improve their service and able to obtain a good star rating and would be a good selling point to the company. The passengers then can make their best choice with confidence when they want to travel. The findings of the same study should be enhanced to other regional areas and should be interpreted with care in the future.